PENGARUH KOMPOS JERAMI PADI DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TERUNG (Solanum melongena L.) - Nadia Rahmi Anwar; Arnis En Yuliai; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research aims to find out the effect of interaction between rice straw compost and NPK fertilizer and get the right dosage for growth and yield of eggplant optimally. The research was conducted at Experimental Garden, Faculty of Agriculture, Riau University, Pekanbaru. The research was conducted for 5 months, from May to September 2018. The research was conducted experimentally in factorial 3 x 3 using a completely randomized design (CRD). The first factor was the dosage of rice straw compost consists of 3 levels (5, 10 and 15 ton.ha-1). The second factor was the dosage of NPK fertilizer (0, 50 and 100 kg.ha-1.). The observed parameterswere plant height, stem diameter, days of flowering, days of harvesting, fruit diameter, fruit length, fruit weight, number of fruits per plant and production per plot. The observed parameters were analyzed byvariance analysis and followed by Duncan's multiple distance test at level 5%. The results of the research showed thatrice straw compostand NPK fertilizer increased the growth of eggplant such as plant height, stem diameter, days of flowering, increased fruit weight, fruit length, number of fruits per plant, production per plot but did not accelerate days of harvesting and did not increase fruit diameter. The treatment of rice straw compost at dosage 5, 10 and 15 tons.ha.-1 and NPK fertilizer at dosage 100 kg.ha.-1 gave better result on the growth and yield of eggplant.Keywords: Eggplant, rice straw compost, NPK fertilizer